2011
DOI: 10.1515/sg-2011-0010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in tree growth, stem form and mortality of Guazuma crinita in slower- and faster-growing plantations in the Peruvian Amazon

Abstract: Guazuma crinita is an important timber tree with a rotation age of 6-12 years in the Peruvian Amazon. A provenance/progeny test containing 200 families from seven locations (provenances) in the Aguaytía watershed of Peru was established in three zones in the Aguaytía watershed that differ in mean annual rainfall and soil fertility. Farmers managed the replications as plantations. Replications were divided into two groups at 24 months: faster-and slower-growing plantations. The faster-growing plantations were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…This is similar to the case of C. spruceanum, which showed much higher genetic variability within than among populations in the Peruvian Amazon (Russell et al 1999). These results are also consistent with results from provenance and provenance/ progeny tests of G. crinita, which showed considerable genetic variation in tree growth and wood density within provenances (Rochon et al 2007, Weber et al 2011.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is similar to the case of C. spruceanum, which showed much higher genetic variability within than among populations in the Peruvian Amazon (Russell et al 1999). These results are also consistent with results from provenance and provenance/ progeny tests of G. crinita, which showed considerable genetic variation in tree growth and wood density within provenances (Rochon et al 2007, Weber et al 2011.…”
Section: Discussionsupporting
confidence: 87%
“…A number of authors have examined both natural stands of tropical trees and cultivated samples (e.g. Hollingsworth A provenance test and a provenance/progeny test of G. crinita were established in the Aguaytia watershed in the Peruvian Amazon Basin to investigate genetic variation in growth and wood density, correlations between growth and density and environmental differences among planting zones in the watershed (Rochon et al 2007, Weber et al 2011. Results from the provenance test indicated that the provenance from the local watershed (Aguaytia) performed better in terms of growth than did provenances from other watersheds in the Peruvian Amazon Basin .…”
Section: Discussionmentioning
confidence: 99%
“…While only a small number of trees of the six provenances was sampled in this study, there were differences in means among provenances, but we did not statistically analyze the difference. Prior to our study, two tests were conducted to investigate genetic variation in growth, wood density, stem form and mortality among provenances (Rochon et al, 2007;Weber and Sotelo-Montes, 2008;Weber et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlations between growth traits at different ages suggest that early selection based on growth could be effective in this species, assuming of course that the growth traits are moderately heritable (Sotelo Montes et al, 2006;Weber et al, 2011). As others have reported (Lambeth, 1980;Riemenschneider, 1988;Matheson et al, 1994), correlations were generally stronger between two consecutive years (e.g.…”
Section: Discussionmentioning
confidence: 67%